Is the Impact of Technological Innovations on Environment Quality Symmetric or Asymmetric? Vietnam and Switzerland Evidence - Tanveer, Zubair; Ahmad, Waheed; Asghar, Nabila; Rehman, Hafeez ur (iRASD Journal of Economics, 2022)
Governments and corporations are investing progressively heavily in research and development for sustainable energy solutions that would increase capital goods efficiency and conserve energy, based on the idea that technological discoveries would successfully decrease deadly greenhouse gas emissions. From 1980 to 2019, the current study investigated symmetrical and asymmetrical relationships between environmental quality, patent, and trademark in Vietnam and Switzerland. ARDL approaches were used, both linear and nonlinear. The outcomes of the nonlinear analysis reveal that asymmetricity exit between technological innovations and environment quality in both Switzerland and Vietnam. In Switzerland, negative shock in the patent has a negative significance, and negative shock in trademarks has positive significant asymmetric effects on CO2 emissions in the short run. In Vietnam, positive shocks in technological innovations have substantial negative asymmetricity with the environmental pollution in the long run. Moreover, positive shocks in both trademark and patent have significant negative, whereas adverse shocks in trademark and patent have positive asymmetric effects on CO2 emissions in the long run. Public policy should fund technological innovations projects, including developing suitable technologies that can create complementarity between increased economic growth and reduced environmental impact.